Transversus Abdominis Plane Block With Liposomal Bupivacaine vs. Regular Anesthetics for Pain Control After Surgery: A Systematic Review and Meta-Analysis - Zhu, Yi; Xiao, Ting; Qu, Shuangquan; Chen, Zheng; Du, Zhen; Wang, Jiangping (Frontiers in Surgery, 2020)
Background: Transverse abdominal plane (TAP) blocks are used to provide pain relief after abdominopelvic surgeries. The role of liposomal bupivacaine (LB) for TAP blocks is unclear. Therefore this study aimed to synthesize evidence on the efficacy of LB vs regular anesthetics in improving outcomes of TAP block. Methods: PubMed, ScienceDirect, Embase, Springer, and CENTRAL databases were searched up to 24th July 2020. Studies comparing LB with any regular anesthetic for TAP block for any surgical procedure and reporting total analgesic consumption (TAC) or pain scores were included. Results: Seven studies including five randomized controlled trials (RCTs) were reviewed. LB was compared with regular bupivacaine (RB) in all studies. A descriptive analysis was conducted for TAC due to heterogeneity in data presentation. There were variations in the outcomes of studies reporting TAC. Meta-analysis of pain scores indicated statistically significant reduction of pain with the use of LB at 12 hours (MD: -0.89 95% CI: -1.44, -0.34 I2=0% p=0.01), 24 hours (MD: -0.64 95% CI: -1.21, -0.06 I2=0% p=0.03), 48 hours (MD: -0.40 95% CI: -0.77, -0.04 I2=0% p=0.03) but not at 72 hours (MD: -0.37 95% CI: -1.31, 0.56 I2=57% p=0.43). Pooled analysis indicated no difference in the duration of hospital stay between LB and RB (MD: -0.18 95% CI: -0.49, 0.14 I2=61% p=0.27). LB significantly reduced the number of days to first ambulation post-surgery (MD: -0.28 95% CI: -0.50, -0.06 I2=0% p=0.01). Conclusions: Current evidence on the role of LB for providing prolonged analgesia with TAP blocks is unclear. Conflicting results have been reported for TAC. LB may result in a small reduction in pain scores up to 48 hours but not at 72 hours. Further high-quality homogenous RCTs are needed to establish high-quality evidence.